Study of oil-water mixtures for oil spill treatment - Lee, Yong Hao (2018)
Oil and water are both basic necessities in everyday life of human beings. Besides being a requirement for life, water has many uses such as in cooking or cleaning. Oil also has its uses in both cooking and operation of machinery. It is most widely produced and consumed as petroleum or diesel, fulfilling the mechanical properties needed by humans. However, it is highly undesirable for oil and water to be mixed together. A mixture of oil and water is usually seen to be useful in terms of cooking. Other forms of mixing would lead to a mechanical failure, such as in machinery where it will not run smoothly and lead to breakdowns. In the worst-case scenario, a mixture of oil and water (such as in an oil spill on the sea), would cause a major biological change in marine lifeforms and hinder processes which purifies seawater into drinking water. For instance, the filtration process of NEWater in Singapore would be highly obstructed if the water being processed contains a large amount of oil. Hence, it is important for oil-water mixtures to be studied and methods to be devised which are efficient in the separation of these mixtures. This study experimentally investigates oil-water mixtures and the separation techniques of said mixtures through a series of experiments and methodologies. Experiments were carried out to ensure a thorough study of these mixtures in the initial phase, gaining knowledge of how molecules of oil and water interact with one another. Following, experiments to separate these molecules from each other are carried out, in a bid to fully separate these mixtures to the highest degree possible, so as to achieve the initial state where both are not mixed together. Further investigations can be done to find better materials exhibiting the same properties so as to make the process more efficient and effective.